PENGARUH KEADILAN ORGANISASI TERHADAP KEPERCAYAAN ORGANISASI (STUDI EMPIRIS PADA SELURUH SEKOLAH TINGGI ILMU EKONOMI DI KOTA PEKANBARU - adi rahmat; hadiyati hadiyati; muhammad rasyid abdillah (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: The purpose of this research is to know the effect of distribution of justice,procedural justice, and interactical juastice to organizational trust. Population in this researchis all lecturer at high school of economics. The sample collection of 104 people. Dataprocessing is done by structural equation modeling analysis using WarpPLS 5.0 software. Theresults showed that organizational justice had positive effect on organizational trust. Thisexplains that subordinates who feel justice in their organization will lead them to believe intheir organization.Keywords: Distributive Justice, Procedural Justice, Interactional Justice, OrganizationalTrust